2015
DOI: 10.1073/pnas.1522150112
|View full text |Cite
|
Sign up to set email alerts
|

Rapid increases in immature synapses parallel estrogen-induced hippocampal learning enhancements

Abstract: Dramatic increases in hippocampal spine synapse density are known to occur within minutes of estrogen exposure. Until now, it has been assumed that enhanced spinogenesis increased excitatory input received by the CA1 pyramidal neurons, but how this facilitated learning and memory was unclear. Delivery of 17β-estradiol or an estrogen receptor (ER)-α (but not ER-β) agonist into the dorsal hippocampus rapidly improved general discrimination learning in female mice. The same treatments increased CA1 dendritic spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
129
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(147 citation statements)
references
References 33 publications
16
129
2
Order By: Relevance
“…Estrogen has been shown to increase the density of dendritic spines on CA1 pyramidal neurons especially following neuronal damage or estrogen loss (Woolley, 1998; Woolley and McEwen, 1992) while estrogen receptor antagonists block this effect (Lewis et al, 1995). The presence of estrogen appears to prime the neuron for new synapse creation through an increase in dendritic spines, however these new spines are only maintained following synapse activation (Phan et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Estrogen has been shown to increase the density of dendritic spines on CA1 pyramidal neurons especially following neuronal damage or estrogen loss (Woolley, 1998; Woolley and McEwen, 1992) while estrogen receptor antagonists block this effect (Lewis et al, 1995). The presence of estrogen appears to prime the neuron for new synapse creation through an increase in dendritic spines, however these new spines are only maintained following synapse activation (Phan et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In behaviorally naïve ovariectomized female mice, it was also found that systemic treatment with 17β-estradiol (Phan et al, 2012), ERα agonist PPT (Phan et al, 2011) and GPER agonist G1 (Gabor, Lymer et al, 2015) rapidly increased dendritic spine density in CA1 field of the hippocampus, while ERβ agonist DPN decreased it (Phan et al, 2011). Subsequently, it was shown that bath application of 17β-estradiol and ERα agonist PPT for 20–30 minutes to hippocampal sections from behaviorally naïve postnatal female (PND 20–32) mice enhanced dendritic spine density (Phan et al, 2015). Intriguingly, within the same timeframe as the dendritic spines and learning enhancements, 17β-estradiol also decreased CA1 hippocampal excitatory input, rapidly and transiently reducing AMPA responses, likely through AMPA receptor internalization (see Figure 2A; Phan et al, 2015).…”
Section: Rapid Action Of Estrogens and Their Receptors: Implicatiomentioning
confidence: 99%
“…Subsequently, it was shown that bath application of 17β-estradiol and ERα agonist PPT for 20–30 minutes to hippocampal sections from behaviorally naïve postnatal female (PND 20–32) mice enhanced dendritic spine density (Phan et al, 2015). Intriguingly, within the same timeframe as the dendritic spines and learning enhancements, 17β-estradiol also decreased CA1 hippocampal excitatory input, rapidly and transiently reducing AMPA responses, likely through AMPA receptor internalization (see Figure 2A; Phan et al, 2015). Hence, it appears new spines induced by estrogens are associated with silent or immature synapses.…”
Section: Rapid Action Of Estrogens and Their Receptors: Implicatiomentioning
confidence: 99%
See 1 more Smart Citation
“…However, in most cases, pre‐acquisition treatment will affect subsequent phases, especially consolidation, because the treatment and/or its downstream products/effects will remain active during this phase. Therefore, to study effects on acquisition, tasks are commonly designed such that testing occurs immediately after learning and/or before consolidation is complete [Lymer JM, Sheppard PAS, Kuun T, et al Estrogens and their receptors in the medial amygdala rapidly promote social recognition in female mice (unpublished)] or results from pre‐ and post‐acquisition treatments are compared. If pre‐acquisition, but not post‐acquisition, treatment affects memory, this would suggest a treatment effect on acquisition but not consolidation.…”
Section: Introductionmentioning
confidence: 99%